A polycationic pillar[5]arene for the binding and removal of organic toxicants from aqueous media. Issue 8 (3rd August 2019) - Fernando, Ashvin; Mako, Teresa L.; Levenson, Adelaide M.; Cesana, Paul T.; Mendieta, Adriana M.; Racicot, Joan M.; DeBoef, Brenton; Levine, Mindy
ABSTRACT: The ability to bind and detect analytes with high levels of selectivity, sensitivity and broad applicability for a variety of analytes is an essential goal, with applications in public health and environmental remediation. Methods to achieve effective binding and detection include electrochemical, and spectroscopic methods. The use of supramolecular chemistry to accomplish such detection, by binding a target in a host and transducing that binding into a measurable signal, has advantages, including tunability of the sensor and the ability to rationally design hosts through an understanding of non-covalent interactions. Reported herein is the design and use of pillar[5]arenes to accomplish precisely such detection. Water-soluble pillar[5]arenes containing 10 cationic linker arms on their periphery bound toxicants in their hydrophobic cores with association constants of 10 5 –10 6 M −1 . With the use of cationic exchange resins, the pillar[5]arene hosts were removed from solution with their encapsulated guests, allowing for effective toxicant removal. GraphicalAbstract: